Beyond the Whistle: Mapping Global Trends in Physical Education Teaching Methods through Bibliometric Analysis - Jian Li; Seong Pek Lim (Physical Education Theory and Methodology, 2025)
Objectives. Focusing on the increasing importance of new pedagogies that incorporate technology, inclusivity, and student-centered approaches, this bibliometric study examines the development and current trends in physical education (PE) teaching methods from 2020 to 2024. In order to guide future research and practice, the study aimed to map the field’s intellectual structure, identify significant contributors, and highlight emergent topics.